Relationship Between Outward Foreign Direct Investment and Domestic Investment: Evidence from GCC Countries - Durani, Farah; Ameer, Waqar; Meo, Muhammad Saeed; Husin, Maizaitulaidawati Md (Asian Economic and Financial Review, 2021)
This paper examines the relationship between outward foreign direct investment and domestic investment, which is regarded with increased interest as a driver of growth in domestic markets for Gulf Cooperation Council (GCC) economies. Mean group (MG), pooled mean group (PMG) and dynamic fixed effect (DFE) approaches have been applied to measure short-run and long-run effects of domestic investment (DI) on outward foreign direct investment (OFDI) by relaxing the assumption of cross-sectional dependence (CD). This research shows that ignoring cross-sectional dependency among the countries which are parallel in economic structure may result in biased economic estimations. The findings of the dynamic fixed effect estimators show that domestic investment has negative and significant effects on FDI outflows in the long run in GCC countries. Furthermore, some of macroeconomic variables (trade and inflation) have insignificant effects on OFDI, whereas human capital has positive and significant effects on FDI outflows in the long run. The findings of this research remain important for policy makers to determine the practical efficacy of market reforms steered towards boosting domestic investment and growth. Furthermore, the policies related to the development of human capital can also take guidance from this study.